Development strategies toward the 21st Century : the experiences and perspectives of developing economies under globalization : papers and proceedings of the International Symposium on development strategies toward the 21st Century- The experiences and perspectives of developing economies under globalization - held on January 30, 2002 at Makuhari, Japan - Yamazawa, Ippei; Amakawa, Naoko (Chiba-shi, Japan : Institute of Developing Economies, Japan External Trade Organization, 2002)
This publication is proceedings of the International Symposium on Development and Strategies toward the 21st Century : the Experiences and Perspectives of Developing Economies under Globalization, held on January 30, 2002 at Makuhari, Japan
IDE-JETRO symposium proceedings No.22
Includes bibliographical references.
lje 24/08/16
Loans
Keywords: Economic development; Globalization; Economic policy; Developing countries; Developing countries